PENGUNGKAPAN Disclosure of Criminal Acts of Online Fraud by Satreskrim Magetan Polres to Create a Precise Police - Pradani, Riri Nabila (Advances in Police Science Research Journal, 2024)
The crime of online fraud is one form Cybercrime is increasing in Indonesia, including in legal areas Magetan Police. Data shows an increase in reports of online fraud cases but only a few have been resolved. This research aims to describes the management of disclosing criminal acts of online fraud by Magetan Police Criminal Investigation Unit, describing the management of Satreskrim personnel in disclosing cases, as well as knowing the influencing factors the disclosure. The research method used is qualitative field research approach and descriptive analysis. The research results show There are still obstacles in disclosing cases such as lack of facilities infrastructure, lack of cooperation with related agencies, lack of members’ in-depth knowledge of cybercrime disclosure, the difficulty of finding evidence and witnesses, and the administrative licensing system which is consuming long time. The suggestions given are adding inventory, increasing quantity and quality of personnel, as well as building cooperation with agencies or competent institution.